FEMINISME DALAM PUPULAN CERPEN NGUNTUL TANAH NULENGEK LANGIT - Intan Apsari, Ni Wayan (Humanis, 2015)
This study discusses Pupulan Cerpen Nguntul Tanah Nulengek Langit (NTNL) with structural analysis and feminism. This analysis aims to reveal the structure of the narrative and feminism contained in NTNL. In this short story in a collection of eleven short stories there, and sources of data in this study there are four short stories are, Nabing, Katiben Ben Teben, Medali Emas and Titah. This study uses structural theory and feminism. The structural theory using a combination of several expert opinions of literature including: Nurgiyantoro, Ratna, and Teeuw, as well as feminist theory by Arif Budiman. Methods and techniques in this study consists of three phases namely, (1) the stage of providing data used method of reading with writing and translation techniques, (2) the stage of data analysis used descriptive analytic method, (3) the stage presentation of the results of data analysis used informal methods of assisted the deductive-inductive techniques. The results obtained in this study the unfolding narrative structure includes plot, character and characterization, setting, theme, and the mandate. In addition, this study also revealed that there are two types of feminism in the NTNL radical feminism and socialist feminism. Radical feminism present in the short story Katiben Ben Teben with character Luh Sari is married to Gusti Ngurah Kusuma with nyentana system. Socialist feminists contained in Nabing stories, and Titah of the Medali Emas characters Men Latri, Wayan Lastri, Men Sari and Luh Sari. The fourth character is struggling to meet the economic needs of the family.
Keywords: short story, structure, feminism